Peran Guru Pendidikan Agama Katolik dalam Meningkatkan Kematangan Emosi Peserta Didik XI IPA SMA Negeri 1 Barusjahe - Br Tarigan, Irda Lias Nita; Sembiring, Mimpin (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
The purpose of this study is to comprehend how Catholic Religious Education (PAK) teachers help students become more emotionally mature. Descriptive qualitative with a qualitative approach is the research methodology employed. At SMA Negeri 1 Barusjahe, 12 informants, students, PAK teachers, and school principals-participated in this study. Data is gathered by observation, interviews, and documentation. An examination of the acquired data utilizing data processing is performed after the procedures of data gathering, reduction, presentation, and conclusion-drawing. The analysis of the data revealed that the PAK teachers' roles included managing classes, facilitating discussions, inspiring students, and serving as positive role models. The study recommends that PAK instructors keep playing a part in helping class XI IPA students at SMA Negeri 1 Barusjahe become more emotionally mature.